Save the date : a novel - Matson, Morgan (Simon & Schuster BFYR, 2019)
When seventeen-year-old Charlie Grant's four older siblings reunite for a wedding, she is determined they will have a perfect weekend before the family home is sold, but last-minute disasters abound.